RECENT ADVANCES IN HOMOLOGICAL FUNCTORS AND CAPABILITY OF GROUPS /cEDITORS Nor Muhainiah Mohd. Ali, Yusof Yaacob ; contributors Nor Muhainiah Mohd. Ali, Rosita Zainal [and 8 others] - Nor Muhainiah Mohd. Ali, editor; Yusof Yaacob, editor; Nor Muhainiah Mohd. Ali, contributor; Rosita Zainal, contributor; Samad Rashid, contributor; Nor Haniza Sarmin, contributor; Hazzirah Izzati Mat Hassim, contributor; Siti Afiqah Mohammad, 1991-, contributor; Adnin Afifi Nawi, 1991-, contributor; Rohaidah Masri, contributor; Abdulqader Mohammed Abdullah Basri, 1978-, contributor; Beuerle, James R., contributor (Johor Bahru, Johor : PENERBIT UTM PRESS, 2015)
Includes bibliographical references and index